Phenotypic and genotypic characterisation of Klebsiella pneumoniae isolated from veterinary and clinical sources / Golnaz Mobasseri - Golnaz , Mobasseri (2021)
Multidrug-resistant (MDR) Klebsiella pneumoniae (K. pneumoniae) poses a serious public health threat. Strains that produce extended-spectrum beta-lactamases (ESBL) are becoming increasingly prevalent among hospital and community-acquired infections. More recently, MDR K. pneumoniae has been isolated from animal sources and potential transmissions between animal and human have also been reported. For better understanding of the importance of “one health” approach, this study described the antimicrobial susceptibility and resistance mechanisms of K. pneumoniae strains isolated from swine farms and a tertiary hospital in Malaysia. The genetic linkages of the strains from different sources were also determined. Swabs from pigs, farmers and environment as well as the feed were collected from 7 swine farms in Peninsular Malaysia. A total of 63 K. pneumoniae strains were isolated with the majority (79.3%) showed resistance to tetracycline. Twenty-two (35%) and 19 (30%) strains were identified as MDR and ESBL-producers, respectively. Among the ESBL producers, the presence of blaTEM (15/19), blaSHV (15/19), blaCTX-M-1 group (7/19) and blaCTX-M-2 group (2/19) have been detected. However, only class 1 integron-encoded integrase was detected. In addition, high resistance to colistin was detected (n=13), where 11 of them were resistant to at least one carbapenem antibiotic. Based on the PCR-sequencing analysis, majority of the colistin-resistant strains harboured blaTEM gene (92.3%), followed by blaSHV (69.23%), blaCTXM-1 (38.46%) and mcr-1 (23.1%). Three colistin-resistant strains had transferable plasmids and colistin-resistant gene, mcr-1. Based on the clustering analysis using Pulsed-Field Gel Electrophoresis (PFGE) and Repetitive Extragenic Palindrome-Polymerase Chain Reaction (REP-PCR), the 63 strains were genetically diverse. However, the clonal relationships of the strains from same sources have been identified. On the other hand, 97 clinical K. pneumoniae strains were analysed for antimicrobial susceptibility, all of which were sensitive to amikacin and colistin (except one strain), while 31.9 % and 27.8 % were MDR and ESBL-producers, respectively. The majority of MDR strains (26/27) were positive for blaTEM, followed by blaSHV (24/27), blaCTX-M-1 group (23/27), blaCTX-M-9 group (2/27) and mcr-1 (1/27). Thirty-seven strains were hypervirulent, and PCR detection of virulence genes showed 38.1 %, 22.7 % and 16.5 % of the strains were positive for K1, wabG and uge genes, respectively. Generally, all the strains were genetically diverse and heterogenous based on clustering analysis. Only seven clusters which comprised of 3-7 strains with high similarity (>80%) have been identified. Finally, one strain each from animal (KP2013Z28) and human (KP2014C46) sources were selected and subjected to whole-genome sequencing. The final draft genome sequences consist of the combined 5,718,777 and 5,455,584 bases with 56.9% and 57.7% G+C content in KP2013Z28 and KP2014C46, respectively. Antimicrobial susceptibility profile of these two K. pneumoniae strains showed resistance to several classes of antibiotics which correlated with genomic analysis that it indicated various antimicrobial resistance genes associated with resistance to various antibiotics. This study has drawn attention to emergence of antimicrobial resistance in clinical setting and animal husbandry which should be taken seriously to prevent the spread and treatment failure due to antimicrobial resistance.